THE INFLUENCE OF PROMOTION ON SALES IMPROVEMENT AT DIANKA BOUTIQUE, SOPPENG REGENCY - Surianti Surianti; Nurmilasari Nurmilasari (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This research aims to analyze the influence of promotion on sales improvement at Dianka Boutique, Soppeng Regency. The study employs a quantitative descriptive method with data collected from 100 respondents who are customers of Dianka Boutique. Data were obtained through questionnaires, interviews, and observations. The results of the study reveal that promotional activities, including advertising, sales promotion, personal selling, and publicity, have a significant effect on increasing sales volume. The study concludes that effective promotional strategies enhance consumer awareness and purchasing interest, which consequently lead to higher sales. This finding highlights the importance of utilizing digital and social media platforms as a cost-effective and efficient promotional